(untitled) (Revista Educação, Artes e Inclusão, 2025)
The present work presents two case studies of students from formal public education who undertook creative processes during Arts classes. It interests to observe in these cases the relationship of the subjects with their creative processes, with the discipline of Arts and their teacher who, and, in a striking way, also the relationship with the School itself. Psychoanalysis is the theoretical framework of this research because it allows a subjective analysis of the relationship of these subjects with the elements of interest. Finally, it was observed that the creative process in the classroom enables learning beyond objectivist goals, involving the subject and his uniqueness at the heart of the activity.